The use and realism of Hryhoriy Skovoroda's fables as one of the facets of Ukrainian cultural heritage during the preparation of future educators (to the 300th anniversary of his birth) - Bakay, S. (New Collegium, 2022)
The article discusses the problem of the relevance and realism of the use of Fables by Hryhoriy Skovoroda during the preparation of future educators. Attention is focused on the modern view of the fable genre in today's conditions. New forms of work with children of senior preschool age are revealed, as musical, poetic and theatrical scenes based on fables, where children can show their creative abilities, skills, skills, and craftsmanship. Attention is focused on the possibility of familiarizing children with cultural, historical heritage and outstanding personalities of Ukraine. In the article, the author emphasizes the concise, personally created poetic text of fables, which highlight the role of the author, the main text (dialogue of the heroes of the fable) and prove the main meaning with the "Skovoroda" morality (power) at the end. The author recommended the use of this scientific, methodological and literary material for children of senior preschool age for teachers of preschool educational institutions and scientists of different pedagogical orientation.